“MATATU THEOLOGY”: MY EXPERIENCE AS A HEKIMA PIONEER LIVING IN ST. JOSEPH THE WORKER PARISH, KANGEMI (Hekima Review, 2024)
We started the first academic year of the newborn “Hekima College” in October 1984. I was a member of the academic staff, mainly as a Lecturer on Pastoral Theology. The main pastoral orientation of the College, given by our Dean, Rev. Fr. Cecil McGarry, SJ, coincided very much with my own vision. We both had the main concern of looking for a theology with a good library and one that was deeply rooted in the African socio-cultural context. Although Fr. McGarry was no longer a young Jesuit, he invested his energies in learning Kiswahili, with such success that he could celebrate Mass and preach in Kiswahili in the neighboring Guadalupe Parish on Sundays, a much-appreciated service he performed during all his years at Hekima.